2020
DOI: 10.1039/d0tb01375g
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of polyoxometalates in multi-functional imaging and photothermal therapy

Abstract: Polyoxometalates as a kind of molecular metal-oxide clusters with precise chemical composition and architecture have been demonstrated to show various potentials in multidisciplinary materials. Accompanying by their direct chemical interaction...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 129 publications
0
29
0
Order By: Relevance
“…The TRIS-MnPOMo-loaded micelles (TRIS-MnPOMo@SPB and TRIS-MnPOMo@SP) were prepared using the dialysis method; this method is one of the best preparation protocols for micelle formation and has been fully studied before. , Based on our knowledge, there is no similar report for entrapping TRIS-MnPOMo in SPB, so it is not easy to verify the results based on evidence. However, some similar studies, such as those reported by Bu et al and Zhang et al, that reported the preparation of other POM-loaded nanoparticles are available.…”
Section: Resultsmentioning
confidence: 94%
“…The TRIS-MnPOMo-loaded micelles (TRIS-MnPOMo@SPB and TRIS-MnPOMo@SP) were prepared using the dialysis method; this method is one of the best preparation protocols for micelle formation and has been fully studied before. , Based on our knowledge, there is no similar report for entrapping TRIS-MnPOMo in SPB, so it is not easy to verify the results based on evidence. However, some similar studies, such as those reported by Bu et al and Zhang et al, that reported the preparation of other POM-loaded nanoparticles are available.…”
Section: Resultsmentioning
confidence: 94%
“…As shown in Figure c and Figure S20, the efficiencies of the core@shell (30%) and lateral heterostructures (24.7%) are much higher than that of the SnS 2 nanoplates (0.47%). This indicates that the photothermal conversion effect mainly arises from the metallic Sn 0.5 Mo 0.5 S 2 nanosheets, where the energy of the excited electrons is released in the form of heat via electron hopping . In addition, based on the calculated work function of SnS 2 (5.2 eV) and Sn 0.5 Mo 0.5 S 2 (4.8 eV), an ohmic contact might form at the SnS 2 /Sn 0.5 Mo 0.5 S 2 heterointerface, affording rapid electron transport in the heterointerface and preventing electron–hole recombination in SnS 2 (Figure d). , Therefore, the photogenerated electrons in SnS 2 are likely transferred to the metallic Sn 0.5 Mo 0.5 S 2 and participate in the above-mentioned heating process.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As it stands, inadequate penetration depths and the low MPE of commonly utilized 808 nm lasers restrict the application of PTT/CDT. Based on standards set by the Food and Drug Administration (FDA), the clinically approved MPE for skin is 0.33 W cm −2 for an 808 nm laser and 1.0 W cm −2 for a 1064 nm laser [ 65 ]. Therefore, research into the development of more effective PTT/CDT has shifted toward identifying nanoplatforms that can take advantage of and increase the therapeutic potential of the deeper penetrating NIR-II biowindow [ 66 , 67 ].…”
Section: Nanoplatforms For Ptt/cdt In the Nir-ii Biowindowmentioning
confidence: 99%